Model Komunikasi Pemerintah Pada Pemanfaatan Instagram dalam Menyampaikan Informasi - Talya Oktarian Asa Putri Imanez; Arif Zainudin; Akhmad Habibullah (Policy, Law and Political Research Center, 2026)
This study is motivated by the principle of good governance, which holds that communication plays a vital role for both the government and the public in conveying information and fostering dialogue to encourage public participation. The government implements two-way communication through the use of social media, which facilitates dialogue and feedback from the public. The objective of this study is to analyze the communication process from the government to the public. This study employs a descriptive qualitative approach using a literature review method. Data were obtained from scientific databases such as Scopus and analyzed using Biblioshiny software to identify publication trends, international collaborations, keywords, communication networks, and the evolving relationships between topics in the scientific literature. The research findings indicate that the government’s communication model regarding the use of Instagram to disseminate information has experienced both improvements and setbacks over the past seven years, with the study revealing that social media has emerged as a platform for communicating on health issues, crisis communication, and public policy. This study shows that the government, as a communicator conveying information via the social media platform Instagram, has not yet been fully effective; its dissemination of information remains focused on one-way communication and has not yet created opportunities for the public to participate.